An easy assay to detect autoantibodies neutralizing cytokines in subjects with critical infections - Donadel, Nicola; Tesser, Alessandra; Valencic, Erica; De Martino, Eleonora; Boz, Valentina; Pin, Alessia; Zorat, Francesca; Pozzato, Gabriele; Tommasini, Alberto (Journal of immunological methods, 2024)
Autoantibodies against type I interferon (IFN) are associated with a worse outcome in COVID-19. The measurement of cytokine-neutralizing autoantibodies has been limited, hindering understanding of their role in clinical practice. We showed that an easy and reliable assay can be reproduced and validated to measure the neutralizing potency of autoantibodies directed to type I or type II IFN. Identifying of anti-cytokine autoantibodies might reflect on early treatments for subsequent infections, such as with antivirals or virus-neutralizing monoclonal antibodies.